Microwave dielectric ceramic material and preparation method thereof

By controlling the mass ratio of SiO2 and B2O3 in microwave dielectric ceramic materials, SiO2 transforms into quartz crystal phase, solving the cracking problem during sintering, and optimizing dielectric properties and improving material stability.

CN119638391APending Publication Date: 2025-03-18SHENZHEN SUNLORD ELECTRONICS
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411894069.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Microwave dielectric ceramic materials are prone to cracking during sintering, mainly due to the volume changes and internal stress increase caused by the differences in structure and density of various variants of SiO2.

Method used

By controlling the mass ratio of SiO2 and B2O3 in microwave dielectric ceramic materials, B2O3 acts as an inducer to promote the transformation of SiO2 into the quartz crystal phase, inhibiting the transformation of SiO2 into the cubic quartz crystal phase, thereby reducing volume changes and internal stress.

Benefits of technology

It effectively reduces the possibility of cracking of microwave dielectric ceramic materials, while optimizing dielectric performance, reducing porosity and dielectric loss, and improving the stability of the resonant frequency temperature coefficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638391A_ABST
    Figure CN119638391A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electronic ceramic materials, and particularly discloses a microwave dielectric ceramic material and a preparation method thereof.The microwave dielectric ceramic material is prepared from, by mass, 75-95 parts of a first main material, 0-18.4 parts of a second main material, 0.03-3.9 parts of B2O3 and 0-13.5 parts of other components, and the first main material is SiO2. When the mass ratio of the B2O3 to the SiO2 is within a specific range, the crystal phase of the SiO2 can be stably converted into a quartz crystal phase, so that the cracking possibility of the microwave dielectric ceramic material is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic ceramic materials, and in particular to a microwave dielectric ceramic material and a preparation method thereof. Background Art

[0002] SiO 2 Because of its low dielectric constant, SiO plays a vital role in microwave dielectric materials. 2 There are many polymorphic variants. During the sintering process, these different SiO 2 The variants are prone to mutual transformation. These variants differ in structure and density. Therefore, the mutual transformation between the variants is usually accompanied by a change in volume, which induces greater internal stress and makes the microwave dielectric ceramic material prone to cracking after sintering. Summary of the invention

[0003] In order to improve the problem that microwave dielectric ceramic materials are prone to cracking after sintering, the invention discloses a microwave dielectric ceramic material and a preparation method thereof.

[0004] In a first aspect, an embodiment of the present invention provides a microwave dielectric ceramic material.

[0005] The microwave dielectric ceramic material is composed of the following components in parts by mass:

[0006] 75-95 parts of the first main ingredient

[0007] 0-18.4 parts of the second main ingredient

[0008] B 2 O 3 0.03~3.9 parts

[0009] The remaining components are 0 to 13.5 parts;

[0010] The first main material is SiO 2 .

[0011] As an optional implementation, in an embodiment of the present invention, the SiO 2 The mass fraction is 75 to 85 parts; 2 O 3 The mass fraction is 0.3 to 3.5 parts.

[0012] As an optional implementation, in an embodiment of the present invention, the SiO 2 The main crystal phase is quartz phase.

[0013] As an optional embodiment, in an embodiment of the present invention, the second main material includes MgO, ZnO, CaO or Al 2 O3 One or more combinations of; and / or,

[0014] The remaining components include Li 2 O, CuO or V 2 O 5 One or more combinations of .

[0015] As an optional implementation, in an embodiment of the present invention, the second main material includes the MgO and the ZnO, the mass fraction of the MgO is 0.1 to 12.7 parts, and the mass fraction of the ZnO is 0.1 to 10.2 parts;

[0016] and / or,

[0017] The remaining components include the Li 2 O, Li 2 The mass fraction of O is 0.5 to 12.2 parts;

[0018] and / or,

[0019] The remaining components include the CuO and the V 2 O 5 , the mass fraction of CuO is 0.01 to 1.6 parts, the V 2 O 5 The mass fraction is 0.05 to 4.5 parts.

[0020] As an optional implementation, in an embodiment of the present invention, the second main material includes the MgO and the ZnO, the mass fraction of the MgO is 1.2 to 11.8 parts, and the mass fraction of the ZnO is 0.8 to 9.1 parts;

[0021] and / or,

[0022] The remaining components include the Li 2 O, Li 2 The mass fraction of O is 2.2 to 12 parts;

[0023] and / or,

[0024] The remaining components include the CuO and the V 2 O 5 , the mass fraction of CuO is 0.05 to 1.4 parts, the V 2 O 5 The mass fraction is 0.5 to 3.6 parts.

[0025] As an optional implementation, in an embodiment of the present invention, the microwave dielectric ceramic material has a dielectric constant of 4.2 to 4.6 at 15 GHz, a dielectric loss of less than 0.2% at 15 GHz, a resonant frequency temperature coefficient of 0 to -15 ppm / °C, and a porosity of less than 0.5%.

[0026] In a second aspect, an embodiment of the present invention provides a method for preparing a microwave dielectric ceramic material.

[0027] A method for preparing a microwave dielectric ceramic material, as described in the first aspect, comprises the following steps:

[0028] The first main material, the second main material and the inducer are mixed, ground with water, dried and sieved to obtain a first premixture, and the first premixture is pre-sintered to form a pre-sintered powder, wherein the inducer is the B 2 O 3 or H 3 BO 3 One or a combination of two;

[0029] The pre-sintered powder is mixed with the remaining components, and then the water-adding grinding, drying and sieving are sequentially performed to obtain a second premix;

[0030] The second premixture and the binder are mixed and granulated and pressed to form a microwave dielectric ceramic precursor, and the formed microwave dielectric ceramic precursor is subjected to secondary sintering to obtain the microwave dielectric ceramic material.

[0031] As an optional implementation, in an embodiment of the present invention, the SiO used to prepare the microwave dielectric ceramic material 2 For gas phase SiO 2 Or quartz phase SiO 2 and / or,

[0032] The sieve used for the screening has a mesh size of 40 to 60 meshes; and / or,

[0033] The drying temperature is 90°C to 120°C; and / or,

[0034] During the pre-sintering process, the temperature is raised to 1000°C to 1100°C at a heating rate of 3°C / min to 6°C / min for pre-sintering for 3h to 4h; and / or,

[0035] During the secondary sintering process, the temperature is first raised to 450°C to 550°C at a heating rate of 3°C / min to 6°C / min and kept warm for 2h to 3h, and then the temperature is raised to 850°C to 900°C at a heating rate of 1°C / min to 3°C / min and kept warm for 2h to 3h to obtain the microwave dielectric ceramic material.

[0036] As an optional embodiment, in an embodiment of the present invention, the second main material includes MgO and ZnO, and the MgO, the ZnO and the SiO 2 Mixing with the inducer, and then entering the water-adding and grinding step;

[0037] and / or;

[0038] The remaining components include CuO, Li 2 O and V 2 O 5 , the pre-sintered powder is mixed with the CuO and the Li 2 O and the V 2 O 5 The pre-sintered powder is mixed, and then the water-added grinding, drying and sieving are sequentially performed to obtain a second pre-mixture containing the pre-sintered powder. The second pre-mixture and the binder are mixed and granulated and pressed to form the microwave dielectric ceramic precursor.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The embodiment of the present invention provides a microwave dielectric ceramic material, wherein SiO 2 and B 2 O 3 Within a specific mass ratio range, it is possible to achieve SiO 2 Effective control of crystal phase transformation. During the sintering process, B 2 O 3 As an inducer, it can promote SiO 2 It mainly transforms to the quartz crystal phase, while significantly inhibiting the SiO 2 The SiO2 phase is a mixture of various phases that transform into a quartz phase, especially between quartz phases or from a quartz phase to a quartz phase. 2 The control of crystal phase transformation can significantly reduce the volume change of microwave dielectric ceramic materials during sintering, thereby effectively reducing the generation of internal stress and reducing SiO 2 The possibility of cracking of microwave dielectric ceramic material as the main material.

[0041] But when B 2 O 3 The proportion of B is too high or too low. 2 O3 Control SiO 2 The effect of crystal phase transformation is poor. 2 The effect of transformation to quartz crystal phase is not obvious, and microwave dielectric ceramic materials are prone to cracking. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0043] Figure 1 This is a SEM (scanning electron microscope) image (10,000 times) of the surface of the microwave dielectric ceramic material of Example 1 of the present invention;

[0044] Figure 2 is a SEM image (10000 times) of a cross section of the microwave dielectric ceramic material of Example 1 of the present invention;

[0045] Figure 3 The XRD (X-Ray Diffraction) spectra of microwave dielectric ceramic materials of some embodiments and some comparative examples disclosed in the present invention. DETAILED DESCRIPTION

[0046] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] In the present invention, the directions or positional relationships indicated by the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal" and the like are based on the directions or positional relationships shown in the drawings. These terms are mainly used to better describe the present invention and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific direction, or to be constructed and operated in a specific direction.

[0048] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those skilled in the art, the specific meanings of these terms in the present invention can be understood according to specific circumstances.

[0049] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0050] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0051] SiO 2 It is a material with a low dielectric constant. A lower dielectric constant can shorten the delay time of electrical signals and increase the operating frequency of microwave dielectric ceramic devices. 2 SiO plays an important role in microwave dielectric ceramic materials. 2 The various variants make it easy to transform into each other during the sintering process. The differences in structure and density between different variants result in the transition between variants usually accompanied by obvious volume changes, which will generate large internal stress and make the microwave dielectric ceramic material easy to crack after sintering.

[0052] To this end, the present invention provides a microwave dielectric ceramic material and a preparation method thereof, so as to overcome the problem that the microwave dielectric ceramic material is prone to cracking after sintering.

[0053] The technical solution of the present invention will be further described below in conjunction with embodiments.

[0054] In a first aspect, an embodiment of the present invention provides a microwave dielectric ceramic material.

[0055] A microwave dielectric ceramic material, which is composed of the following components in parts by mass:

[0056] 75-95 parts of the first main ingredient

[0057] 0-18.4 parts of the second main ingredient

[0058] B 2 O 3 0.03~3.9 parts

[0059] The remaining components are 0 to 13.5 parts;

[0060] The first main material is SiO2 .

[0061] The present invention finds that SiO in microwave dielectric ceramic materials 2 and B 2 O 3 Within a specific mass ratio range, it is possible to achieve SiO 2 Effective control of crystal phase transformation. During the sintering process, B 2 O 3 As an inducer, it can promote SiO 2 It mainly transforms to the quartz crystal phase, while significantly inhibiting the SiO 2 The SiO2 phase is amorphous and is amorphous phase. 2 The control of crystal phase transformation can significantly reduce the volume change of microwave dielectric ceramic materials during sintering, thereby effectively reducing the generation of internal stress and reducing the use of SiO 2 The possibility of cracking of microwave dielectric ceramic material as the main material.

[0062] For example, SiO 2 The mass fractions of B are 75, 78, 80, 82, 85, 88, 90, 92 or 95. 2 O 3 The mass fraction is 0.03 parts, 0.08 parts, 0.12 parts, 0.5 parts, 1.6 parts, 2.3 parts, 2.9 parts, 3.5 parts or 3.9 parts.

[0063] When B 2 O 3 The proportion of B is too high or too low. 2 O 3 Control SiO 2 The effect of crystal phase transformation is poor. 2 The effect of transformation to quartz crystal phase is not obvious, and microwave dielectric ceramic materials are prone to cracking.

[0064] In some embodiments, SiO 2 The mass fraction of B is 75 to 85 parts; 2 O 3 The mass fraction is 0.3 to 3.5 parts.

[0065] Through SiO 2 and B 2 O 3 The mass ratio of B 2 O 3 For SiO 2 The crystal phase transformation control effect during the sintering process is better, which is beneficial to the SiO 2The proportion of the crystal phase stably transformed into the quartz crystal phase can reduce the volume change of the ceramic material and the generation of internal stress during the sintering process, thereby further reducing the possibility of cracking of the microwave dielectric ceramic material, and can also better reduce the porosity and dielectric loss, and improve the resonant frequency temperature coefficient.

[0066] In some embodiments, SiO 2 The main crystal phase is quartz phase.

[0067] The present invention controls B 2 O 3 and SiO 2 The ratio of SiO 2 The main crystal phase of SiO is transformed into quartz crystal phase. 2 The mutual transformation between various variants is effectively suppressed, thereby reducing the possibility of cracking of microwave dielectric ceramic materials.

[0068] In some embodiments, the second main material includes MgO, ZnO, CaO or Al 2 O 3 One or more combinations of .

[0069] In some embodiments, the second main material includes MgO and ZnO, the mass fraction of MgO is 0.1 to 12.7 parts, and the mass fraction of ZnO is 0.1 to 10.2 parts. 2 The combination of components can reduce the sintering temperature of the microwave dielectric ceramic material and improve the density of the microwave dielectric ceramic material at a low sintering temperature.

[0070] Exemplarily, the mass fraction of MgO is 0.1, 0.7, 2.5, 3.7, 6.5, 8.9, 10.2 or 12.7 parts, and the mass fraction of ZnO is 0.1, 0.7, 2.5, 3.7, 6.5, 8.9 or 10.2 parts.

[0071] In some embodiments, the remaining components include MgO and ZnO, the mass fraction of MgO is 1.2 to 11.8 parts, and the mass fraction of ZnO is 0.8 to 9.1 parts.

[0072] By further limiting the dosage range of MgO and ZnO, the density of the microwave dielectric ceramic material at a low sintering temperature can be better reduced.

[0073] In some embodiments, the remaining components include Li 2 O, Li 2 The mass fraction of O is 0.5 to 12.2 parts.

[0074] The above mass fraction of Li 2The addition of O can improve the density of microwave dielectric ceramic materials at low sintering temperatures and improve the performance of microwave dielectric ceramic materials. 2 The mass fraction of O is 2.2 to 12 parts.

[0075] In some embodiments, the remaining components also include CuO and V 2 O 5 , the mass fraction of CuO is 0.01 to 1.6 parts, V 2 O 5 The mass fraction is 0.05 to 4.5 parts.

[0076] Through CuO and V 2 O 5 The combination is beneficial to further reduce the porosity and improve the density at low sintering temperature. It is also beneficial to reduce dielectric loss and improve the application effect of microwave dielectric ceramic materials.

[0077] In some embodiments, the remaining components include CuO and V 2 O 5 , the mass fraction of CuO is 0.05 to 1.4 parts, V 2 O 5 The mass fraction is 0.5 to 3.6 parts.

[0078] By further defining CuO and V 2 O 5 The dosage range of Li 2 O with CuO and V 2 O 5 The combined effect is better and can significantly reduce the dielectric loss of microwave dielectric ceramic materials.

[0079] For example, Li 2 The mass fraction of O is 0.5, 1.3, 3.5, 5.6, 7.9 or 12.2 parts, the mass fraction of CuO is 0.01, 0.2, 0.9 or 1.6 parts, V 2 O 5 The mass parts are 0.05 parts, 0.1 parts, 0.5 parts, 1 parts, 3 parts or 4.5 parts.

[0080] It should be noted that in the microwave dielectric ceramic material, the remaining components include the first main material, the second main material and B 2 O 3 The remaining components can include Li 2 O, CuO and V 2 O 5 In addition, it may also contain components formed in the microwave dielectric ceramic material after sintering, such as silicate components such as zinc silicate or magnesium silicate.

[0081] In some embodiments, the microwave dielectric ceramic material has a dielectric constant of 4.2 to 4.6 at 15 GHz, a dielectric loss of less than 0.2% at 15 GHz, a resonant frequency temperature coefficient of 0 to -15 ppm / °C, and a porosity of less than 0.5%.

[0082] The dielectric constant, dielectric loss, resonant frequency temperature coefficient and porosity of the microwave dielectric ceramic material of the present invention can be simultaneously controlled within the above ranges, which can better meet the use requirements of low dielectric constant, low dielectric loss, low porosity, etc. of the microwave dielectric ceramic material.

[0083] In a second aspect, an embodiment of the present invention provides a method for preparing a microwave dielectric ceramic material.

[0084] A method for preparing a microwave dielectric ceramic material, such as the method for preparing a microwave dielectric ceramic material mentioned in the first aspect, comprises the following steps:

[0085] The first main material, the second main material and the inducer are mixed, ground with water, dried, and sieved to obtain a first premixture, and the first premixture is pre-sintered to form a pre-sintered powder, wherein the inducer is B 2 O 3 or H 3 BO 3 One or a combination of two;

[0086] The pre-sintered powder is mixed with the remaining components, and then ground with water, dried and sieved in sequence to obtain a second pre-mixture;

[0087] The second premixture and the binder are mixed and granulated and pressed to form a microwave dielectric ceramic precursor, and the formed microwave dielectric ceramic precursor is subjected to secondary sintering to obtain a microwave dielectric ceramic material.

[0088] The induction agent for preparing the above microwave dielectric ceramic material can be H 3 BO 3 or B 2 O 3 During the sintering process, H 3 BO 3 Will be decomposed into B 2 O 3 , in order to achieve the SiO 2 Effective control of the crystal phase structure transformation makes SiO 2 The crystal phase transforms to the quartz crystal phase. The control of the crystal phase transformation is conducive to reducing volume change and internal stress, reducing the possibility of cracking of microwave dielectric ceramic materials after sintering, and also reducing the porosity and dielectric loss of microwave dielectric ceramic materials, optimizing the resonant frequency temperature coefficient to make the resonant frequency temperature coefficient closer to zero. After sintering is completed, the above-mentioned inducing agents are converted into B2 O 3 The form of ferrite exists in microwave dielectric ceramic materials.

[0089] When preparing the raw materials of microwave dielectric ceramic materials, if H 3 BO 3 As an inducer, it is necessary to 2 O 3 The expected mass of H 3 BO 3 The amount of addition is to ensure that the quality of the final product meets the expected standards.

[0090] In some embodiments, the adhesive includes one or more of PMMA (polymethyl methacrylate) adhesive, PVB (polyvinyl butyral) adhesive, or PVA (polyvinyl alcohol) adhesive.

[0091] In some embodiments, SiO used in preparing microwave dielectric ceramic materials 2 For gas phase SiO 2 Or quartz phase SiO 2 .

[0092] By choosing a specific type of SiO 2 Raw materials can be used for SiO 2 The crystal phase structure can be more effectively controlled, the volume change and internal stress during the sintering process can be reduced, and the quality of the microwave dielectric ceramic material after sintering can be improved.

[0093] In some embodiments, the mesh size used for sieving is 40-60 mesh. Screening the powder material is helpful to improve the fineness of the powder material, thereby improving the quality of the microwave dielectric ceramic material after sintering.

[0094] In some embodiments, the drying temperature is 90° C. to 120° C. After the water-adding grinding process, this temperature is conducive to evaporating water, thereby achieving rapid drying of the raw materials after the grinding process.

[0095] In some embodiments, during the pre-sintering process, the temperature is raised to 1000° C. to 1100° C. at a heating rate of 3° C. / min to 6° C. / min for pre-sintering for 3 h to 4 h.

[0096] Under the above-mentioned pre-sintering conditions, the activity of each raw material is enhanced, which is conducive to the formation of a preliminary bond between the raw materials, reducing the temperature required for the subsequent secondary sintering. At the same time, it reduces the volume change caused by the mutual bonding between the raw materials during the secondary sintering process, further reducing the possibility of cracking of the microwave dielectric ceramic material.

[0097] During the secondary sintering process, the temperature is first raised to 450°C~550°C at a heating rate of 3°C / min~6°C / min and kept for 2h~3h, and then the temperature is raised to 850°C~900°C at a heating rate of 1°C / min~3°C / min and kept for 2h~3h to obtain a microwave dielectric ceramic material.

[0098] In some embodiments, the second main material is MgO and ZnO. 2 Mix with the inducer and then enter the water adding and grinding step.

[0099] and / or;

[0100] The remaining components are CuO, Li 2 O and V 2 O 5 , pre-sintered powder and CuO, Li 2 O and V 2 O 5 The mixture is mixed, and then water-grinded, dried and sieved in sequence to obtain a second premix containing pre-sintered powder. The second premix and a binder are mixed, granulated and pressed to form a microwave dielectric ceramic precursor.

[0101] The technical solution of the present invention will be further described below in conjunction with more specific embodiments.

[0102] Example 1 to Example 6

[0103] The microwave dielectric ceramic materials of Examples 1 to 6 provided by the present invention are prepared according to the following steps:

[0104] Take SiO 2 , H 3 BO 3 , MgO and ZnO are mixed, deionized water is added as a solvent to prepare a first slurry, the first slurry is transferred to a ball mill for grinding, and then placed in a drying oven, dried at 100° C., and after drying, passed through a 40-mesh sieve to obtain a first premixed powder;

[0105] The first premixed powder is heated from room temperature to 1050°C at a rate of 5°C / min for pre-sintering for 4 hours, and then naturally cooled to room temperature to obtain pre-sintered powder;

[0106] The pre-sintered powder and Li 2 O, add deionized water as a solvent to prepare a second slurry, transfer the second slurry to a ball mill for grinding, then place it in a drying oven, dry it at 100°C, and pass it through a 40-mesh sieve after drying to obtain a second premixed powder;

[0107] The second premixed powder and PVA adhesive are mixed and granulated in a mass ratio of 5:1, and dry-pressed to obtain a round block-shaped microwave dielectric ceramic precursor sample with a diameter of 14 mm ± 0.2 mm and a height of 3 mm ± 0.2 mm. The sample is heated to 500 ° C at a heating rate of 3.5 ° C / min and kept warm for 2 h, and then heated to 900 ° C at a heating rate of 1.5 ° C / min and kept warm for 2 h to obtain a microwave dielectric ceramic material.

[0108] In Examples 1 to 6, the raw material ratios for preparing microwave dielectric ceramic materials are different, and the specific amounts of each raw material are shown in Table 1.

[0109] Example 7 to Example 12

[0110] The microwave dielectric ceramic materials of Examples 7 to 12 provided by the present invention are prepared according to the following steps:

[0111] Take SiO 2 , H 3 BO 3 , MgO and ZnO are mixed, deionized water is added as a solvent to prepare a first slurry, the first slurry is transferred to a ball mill for grinding, and then placed in a drying oven, dried at 100° C., and after drying, passed through a 40-mesh sieve to obtain a first premixed powder;

[0112] The first premixed powder is heated from room temperature to 1050°C at a heating rate of 5°C / min for 4 hours, and then naturally cooled to room temperature to obtain a pre-sintered powder;

[0113] Take the above pre-sintered powder and Li 2 O, CuO, V 2 O 5 Mix, add deionized water as a solvent to prepare a second slurry, transfer the second slurry to a ball mill for grinding, then place in a drying oven, dry at 100° C., and pass through a 40-mesh sieve after drying to obtain a second premixed powder;

[0114] The second premixed powder and PVA adhesive are mixed and granulated in a mass ratio of 5:1, and dry-pressed to obtain a round block-shaped microwave dielectric ceramic precursor sample with a diameter of 14 mm ± 0.2 mm and a height of 3 mm ± 0.2 mm. The sample is heated to 500 °C at a heating rate of 3.5 °C / min and kept warm for 2 h, and then heated to 900 °C at a heating rate of 1.5 °C / min and kept warm for 2 h to obtain a microwave dielectric ceramic material.

[0115] In Examples 7 to 12, the raw material ratios for preparing microwave dielectric ceramic materials are different, and the specific amounts of each raw material are shown in Table 1.

[0116] Comparative Example 1

[0117] This comparative example provides a microwave dielectric ceramic material, which differs from Example 2 in that: no H 3 BO 3 , the rest are consistent with Example 2.

[0118] Comparative Example 2

[0119] This comparative example provides a microwave dielectric ceramic material, which is different from Example 2 in that: 3 BO 3 The input amount is different, see Table 1 for details, and the rest is consistent with Example 2.

[0120] Comparative Example 3

[0121] This comparative example provides a microwave dielectric ceramic material, which is different from Example 5 in that: 3 BO 3 The input amount is different, see Table 1 for details, and the rest is consistent with Example 5.

[0122] Comparative Example 4

[0123] This comparative example provides a microwave dielectric ceramic material, which is different from Example 11 in that: 3 BO 3 The input amount is different, see Table 1 for details, and the rest is consistent with Example 11.

[0124] In Comparative Examples 1 to 4, the specific amounts of the raw materials used to prepare the microwave dielectric ceramic materials are shown in Table 1.

[0125] Table 1

[0126]

[0127]

[0128] Experiment 1

[0129] The microwave dielectric ceramic material sample prepared according to the scheme described in Example 1 was subjected to SEM test on the surface and cross section of the sample. The test results are shown in Figure 1 and Figure 2 .

[0130] Depend on Figure 1 It can be seen that there is no crack on the surface of the microwave dielectric ceramic material sample, and combined with Figure 2 It can be seen that there are basically no holes on the surface and cross-section of the microwave dielectric ceramic material sample, and the sintering is dense, which is beneficial to improving the strength of the microwave dielectric ceramic material sample.

[0131] Experiment 2

[0132] Microwave dielectric ceramic material samples were prepared according to the schemes described in Example 1, Example 2, Example 4, Example 8, Example 12, Comparative Example 1 and Comparative Example 2, and XRD analysis was performed on these samples. The XRD analysis results are shown in Figure 3 .

[0133] Figure 3 The horizontal axis close to the diffraction angle of 25° represents SiO 2 The cristobalite phase, the horizontal axis close to 30° diffraction angle represents SiO 2 By comparison Figure 2 It can be seen from the experimental results of each embodiment and comparative example that the main crystal phase of embodiment 1, embodiment 2, embodiment 4, embodiment 8 and embodiment 12 is quartz crystal phase, and the main crystal phase of comparative example 1 and comparative example 2 is cristobalite crystal phase. Compared with embodiment 2, comparative example 1 and comparative example 2 only change H 3 BO 3 dosage, which proves that changing H 3 BO 3 The amount of SiO 2 The crystal phase is controlled by H 3 BO 3 With SiO 2 The mass ratio of SiO 2 The crystal phase transformation of SiO 2 The problem that the microwave dielectric ceramic material prepared as the main material is easy to crack is solved, and the reliability of the microwave dielectric ceramic material is improved.

[0134] Experiment 3

[0135] According to the schemes described in the above embodiments and comparative examples, microwave dielectric ceramic material samples were prepared, and relevant performance tests were performed on the prepared microwave dielectric ceramic material samples, as follows:

[0136] 3.1. Test the porosity of microwave dielectric ceramic material samples by boiling method.

[0137] 3.2. The dielectric constant, dielectric loss and resonant frequency temperature coefficient of microwave dielectric ceramic material samples at 15 GHz were tested by using a microwave network analyzer.

[0138] 3.3. Observe with human eyes whether the microwave dielectric ceramic material sample is cracked.

[0139] The above test results are recorded in Table 2.

[0140] Table 2

[0141]

[0142] It can be seen from the test results in Table 2 that Examples 1 to 12 have lower porosity, dielectric constant and dielectric loss, the resonant frequency temperature coefficient is close to zero, and the material has no cracking phenomenon, which can better meet the use requirements of microwave devices.

[0143] Compared with Example 2, Comparative Example 1 and Comparative Example 2 only changed H 3 BO 3 The addition amount of microwave dielectric ceramic material after sintering showed obvious cracking. Figure 3 The results show that by controlling the SiO 2 The crystal phase of SiO 2 The main crystal phase is transformed into the quartz crystal phase, which can significantly reduce the possibility of cracking of microwave dielectric ceramic materials.

[0144] Further comparison of the test results of Example 5 and Comparative Example 3, and Example 11 and Comparative Example 4 in Table 2 shows that H 3 BO 3 The dosage of SiO 2 The crystal phase of 3 BO 3 The amount of B in the microwave dielectric ceramic material after sintering is ensured. 2 O 3 With SiO 2 The mass ratio of SiO is within a specific range, which can effectively control the 2 The crystal phase reduces the possibility of cracking of microwave dielectric ceramic materials. 3 BO 3 Too much or too little amount of B in the sintered microwave dielectric ceramic material 2 O 3 With SiO 2 If the mass ratio of SiO exceeds a certain range, it is impossible to control 2 Due to the crystal phase, microwave dielectric ceramic materials are prone to cracking.

[0145] From the comparison of the test results of Examples 1-6 and Examples 7-12 in Table 2, it can be seen that adding appropriate proportions of CuO and V to the microwave dielectric ceramic material 2 O 5 After that, the dielectric loss of the material can be further reduced and the dielectric properties of microwave dielectric ceramic materials can be improved.

[0146] The microwave dielectric ceramic material and the preparation method thereof disclosed in the embodiments of the present invention are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the microwave dielectric ceramic material and the preparation method thereof and the core idea of ​​the present invention. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A microwave dielectric ceramic material, characterized in that: The microwave dielectric ceramic material is composed of the following components in parts by mass: 75-95 parts of the first main ingredient 0-18.4 parts of the second main ingredient B2O3 0.03~3.9 parts The remaining components are 0 to 13.5 parts; The first main material is SiO2.

2. The microwave dielectric ceramic material according to claim 1, characterized in that: The mass fraction of the SiO2 is 75 to 85 parts; the mass fraction of the B2O3 is 0.3 to 3.5 parts.

3. The microwave dielectric ceramic material according to claim 1, characterized in that: The main crystal phase of the SiO2 is a quartz crystal phase.

4. The microwave dielectric ceramic material according to claim 1, characterized in that: The second main material comprises one or more combinations of MgO, ZnO, CaO or Al2O3; and / or, The remaining components include one or a combination of Li2O, CuO or V2O5.

5. The microwave dielectric ceramic material according to any one of claims 1 to 4, characterized in that: The second main material includes the MgO and the ZnO, the mass fraction of the MgO is 0.1 to 12.7 parts, and the mass fraction of the ZnO is 0.1 to 10.2 parts; and / or, The remaining components include Li2O, and the mass fraction of Li2O is 0.5 to 12.2 parts; and / or, The remaining components include the CuO and the V2O5, the mass fraction of the CuO is 0.01 to 1.6 parts, and the mass fraction of the V2O5 is 0.05 to 4.5 parts.

6. The microwave dielectric ceramic material according to any one of claims 1 to 4, characterized in that: The second main material includes the MgO and the ZnO, the mass fraction of the MgO is 1.2 to 11.8 parts, and the mass fraction of the ZnO is 0.8 to 9.1 parts; and / or, The remaining components include Li2O, and the mass fraction of Li2O is 2.2 to 12 parts; and / or, The remaining components include the CuO and the V2O5, the mass fraction of the CuO is 0.05 to 1.4 parts, and the mass fraction of the V2O5 is 0.5 to 3.6 parts.

7. The microwave dielectric ceramic material according to any one of claims 1 to 4, characterized in that: The dielectric constant of the microwave dielectric ceramic material at 15 GHz is 4.2-4.6, the dielectric loss at 15 GHz is less than 0.2%, the resonant frequency temperature coefficient of the microwave dielectric ceramic material is 0--15 ppm / °C, and the porosity of the microwave dielectric ceramic material is less than 0.5%.

8. A method for preparing a microwave dielectric ceramic material, characterized in that: The method for preparing the microwave dielectric ceramic material according to any one of claims 1 to 7 comprises the following steps: The first main material, the second main material and the inducer are mixed, ground with water, dried and sieved to obtain a first premixture, and the first premixture is pre-sintered to form a pre-sintered powder, wherein the inducer is one of B2O3 or H3BO3 or a combination of the two; The pre-sintered powder is mixed with the remaining components, and then the water-adding grinding, drying and sieving are sequentially performed to obtain a second premix; The second premixture and the binder are mixed and granulated and pressed to form a microwave dielectric ceramic precursor, and the formed microwave dielectric ceramic precursor is subjected to secondary sintering to obtain the microwave dielectric ceramic material.

9. The method for preparing a microwave dielectric ceramic material according to claim 8, characterized in that: The SiO2 used in preparing the microwave dielectric ceramic material is gas phase SiO2 or quartz phase SiO2; and / or, The sieve used for the screening has a mesh size of 40 to 60 meshes; and / or, The drying temperature is 90°C to 120°C; and / or, During the pre-sintering process, the temperature is raised to 1000°C to 1100°C at a heating rate of 3°C / min to 6°C / min for pre-sintering for 3h to 4h; and / or, During the secondary sintering process, the temperature is first raised to 450°C to 550°C at a heating rate of 3°C / min to 6°C / min and kept warm for 2h to 3h, and then the temperature is raised to 850°C to 900°C at a heating rate of 1°C / min to 3°C / min and kept warm for 2h to 3h to obtain the microwave dielectric ceramic material.

10. The method for preparing a microwave dielectric ceramic material according to claim 8, characterized in that: The second main material includes MgO and ZnO, and the MgO, the ZnO, the SiO2 and the inducer are mixed, and then enter the water-adding grinding step; and / or; The remaining components include CuO, Li2O and V2O5. The pre-sintered powder is mixed with the CuO, Li2O and V2O5, and then the water-added grinding, drying and sieving processes are carried out in sequence to obtain a second premixture containing the pre-sintered powder. The second premixture and the binder are taken to carry out the mixed granulation and the compression molding processes to form the microwave dielectric ceramic precursor.

Citation Information

Cited By

  • Electronic ceramic material based on calcined alpha-Al2O3 and preparation method thereof

    CN120247537A

  • An electronic ceramic material based on calcined α-Al2O3 and its preparation method

    CN120247537B